Quality of education and professional competences of teachers: a sociological approach - Soyka, Nastassiya D. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The problems arising between the professional competencies of teachers and the quality of education are shown the solution to which can be found through the use of sociological research methods. The results of the study of teachers’ satisfaction with the quality of education and the effectiveness of advanced training courses, conducted by the author of this article, are analysed. The reasons for the impossibility of fully realising the educational needs of teachers in the process of educational activities are revealed, the low practical effectiveness of advanced training plans is noted. A contradiction is revealed between teachers’ awareness of the importance of advanced training and the practical application of the knowledge acquired in its course which arises due to the underdevelopment of professional competencies of teachers. A conclusion is made about the importance of using a sociological approach to studying the problems of the education system.
Keywords: quality of education; professional self-realisation; professional competencies; information and communication technologies; educational process; sociological approach